Semantically Enhanced Information Portal for Community of University Researchers - Paweloszek, Ilona (Semantycznie wzbogacony portal informacyjny dla społeczności pracowników naukowych uniwersytetu, 2011)
The work of university researchers can be supported by using information portals based on open architectures. The portals can be enhanced and developed by exploiting Web Services, semantic technologies, mashup or microblogging technologies. The aim of this paper is to present selected tools and techniques for semantic enrichment of information portal that would serve community of university researchers, teams and students, to support their individual and collaborative work. First the paper addresses the general characteristics of the community software and Semantic Web. Next the required functionalities of the portal are presented followed by brief description of methodologies and technologies proposed for implementation of the functionalities in practice. Solutions are described on the example of the Czestochowa University of Technology.
Keywords: pracownicy naukowi; portale internetowe; sieć semantyczna; szkolnictwo wyższe; academic staff; web portals; semantic web service (sws); higher education